Faithless - Karin Slaughter 1971- (UK Arrow Books, 2006)
The victim was buried alive in the Georgia woods then killed in a horrifying fashion. When Sara Linton and Jeffrey Tolliver stumble upon the body, both become consumed with finding out who killed the pretty, impeccably dressed young woman. And for Sara and Jeffrey, a harrowing journey begins, one that will test their own turbulent relationship and draw dozens of lives into the case.Lena Adams is one of them. A Grant County detective for years, she has her own reasons for being
Keywords: Literature (3GdCOHs; General -- Fiction; Tolliver, Jeffrey (Fictitious character); Linton, Sara (Fictitious character) -- Fiction; Police chiefs -- Fiction; Women physicians -- Fiction; Young women -- Crimes against -- Fiction; Police -- Georgia -- Fiction; Forensic pathologists -- Fiction